A preliminary investigation on the antimicrobial activity of buyo (Piper Betle) leaves. - Lisao, Nestor S. Jr
From standard aqueous extract were tested on four test organisms namely: Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus saprophyticus, and Candida albicans. Positive controls were 6mg/ml of Amoxicillin and 6mg/ml of mycostatin for Staphylococcus and Candida albicans respectively. All the test organisms were subjected to the filter paper disk agar method. Zone of inhibition was the determinant for the effectivity of these concentrations. (p)Extract concentrations of 75 25 50 75 and 0 Aqueous extracts of Piper betle of different concentrations (100 and 100 exhibited weak inhibition on Staphylococcus aureus, Staphylococcus epidermis, and Candida albicans. Negative result was observed for Staphylococcus saprophyticus, where zone of inhibition was observed.